Integrated Financial Strategies: Sinking Funds and Annuity Pricing in a Dynamic Market Environment - Bilhaq, Saskia Iqlima; Muthmainah, Rona Afiya (International Journal of Mathematics, Statistics, and Computing, 2024)
The study on "Integrated Financial Strategies: Sinking Funds and Annuity Pricing in a Dynamic Market Environment" seeks to investigate how sinking funds, annuity pricing, and dynamic market environments can be integrated within the context of integrated financial strategies. The study focuses on the following areas: (1) the application of actuarial tables and probability distributions to ascertain the proper values for annuities payments and sinking fund balances; (2) the role of the actuary science in sinking funding scheduling; (3) the effect of market factors, such as interest rates, inflation, and economic conditions, on the value and value of sinking investments; (4) the analysis of the relationship between market dynamics, including interest rates and time periods, and the value of a sinking asset, including the integration of the two financial instruments. The analysis revealed that changes in the interest rate and the number of periods directly influence the future value of the sinking assets. The integration of these financial instruments can help to optimize financial decision-making, enhance risk management, increase investment returns, improve financial planning, and lead to greater integration with other financial instruments, ultimately leading to better financial outcomes for both financial professionals and investors